DEVELOPMENT OF LEADERSHIP QUALITIES THROUGH METHODS OF DIRECT EXPERIENCE OF LIVE LIVING - Balte-Balciuniene, Rasa; Kharitonova, Tatiana (PEOPLE: International Journal of Social Sciences, 2020)
The purpose of this study was to examine the problem of formation of special mindset of the leader. The training of leaders (AUTHENTICUS program, HAI.LT institute) is focused on the shaping of independent decision-making and freedom from stereotypes. In order to break out from automatic reactions of the brain and create novelty we taught leaders to reflect on his/her emotional reactions that arise in situations of real life – live living. AUTHENTICUS program of consciousness leadership is a modular training program held by HAI.LT Institute since 2011. We conducted psychological study of participants of leadership training program (44 leaders, 2013 - 2015). Results of the study showed the changes in value orientations, in the behavioral priorities in the locus of control, also in the stereotypical beliefs, and motivation of decisions.